STRUCTURAL ENVIRONMENT OF NB5+ IN DRY AND FLUID-RICH (H2O, F) SILICATE GLASSES: A COMBINED XANES AND EXAFS STUDY - Piilonen P.C.; Farges F.; Brown G.E.; Linnen R.L.; Pawlak M.; Pratt A. (My University, 2006)
We performed Nb K-edge XAFS spectroscopy experiments on a series of model compounds, natural glasses and anhydrous and fluid-bearing (H2O, F) synthetic glasses doped with 0.1 to 5 wt.% Nb2O5. In addition, we decribe a new ICP-AES method to provide chemical information on micro quantities of glass samples. In dry, H2O- and F-bearing peraluminous and peralkaline glasses, Nb5+ is present as NbO6 moeties. These share corners with SiO4 and AlO4 tetrahedra through non-bridging oxygen (NBO) atoms. No evidence for 4-, 5- or 7-coordinated Nb was found. Slight changes in site centrosymmetry were detected among the compositions (ordered in NBO-rich compositions, more disordered and distorted in peraluminous ones). In agreement with Nb2O5 solubility experiments, bond-valence theory suggests that network-modifying cations such as Na are present in the vicinity of Nb. This environment most closely resembles those observed in alkali niobosilicates such as vuonnemite and labuntsovite-group minerals. In dry, peraluminous glasses, the sites containing Nb are disordered, as in columbite. Similar information on speciation was obtained for a set of natural glasses. The local environment around the Nb atoms is therefore highly sensitive to melt depolymerization, alkalinity and H2O, F contents, all of which will increase the solubility of Nb in the melt and explains a number of its geochemical properties in evolved magmatic systems.